Planting Seeds for Food Is Medicine: Pre-Implementation Planning Methods and Formative Evaluation Findings From a Multi-Clinic Initiative in the Midwest - Marianna S. Wetherill; Kristina M. Bridges; Gabrielle E. Talavera; Susan P. Harvey; Brandon Skidmore; Elizabeth Stewart Burger (SAGE Publishing, 2024)
Food is medicine (FIM) initiatives are an emerging strategy for addressing nutrition-related health disparities increasingly endorsed by providers, payers, and policymakers. However, food insecurity screening protocols and oversight of medically-tailored food assistance programs are novel for many healthcare settings. Here, we describe the pre-implementation planning processes used to successfully engage federally-qualified health centers (FQHCs) across Kansas to develop new FIM initiatives. A Kansas-based philanthropic foundation facilitated pre-implementation planning for FQHCs over 17 months across 3 stages: 1) Community inquiry, 2) FIM learning event with invitation for FQHC attendees to request pre-implementation funding, and 3) Pre-implementation planning workshops and application assignments for FQHC grantees to develop a FIM implementation grant proposal. We evaluated satisfaction and perceived utility of these pre-implementation planning activities via post-workshop surveys and qualitative comparisons of FIM design components from pre-implementation and implementation grant applications. All 7 FQHCs attending the learning event applied for and were awarded pre-implementation planning grants; 6 submitted an implementation grant application following workshop completion. FQHCs rated pre-implementation support activities favorably; however, most clinics cited limited staff as a barrier to effective planning. As compared to pre-implementation planning grant proposals, all FQHCs elected to narrow their priority population to people with pre-diabetes or diabetes with better articulation of evidence-based nutrition prescriptions and intervention models in their final program designs. In the midst of a nationwide FIM groundswell, we recommend that funders, clinic stakeholders, and evaluators work together to devise and financially support appropriate pre-implementation planning activities prior to launching new FIM initiatives.